(untitled) (Albayan Scientific Journal, 2025)
The study aimed to identify the challenges faced by the Academic Training and Development Center in delivering training programs for academic leaders at Al-Mahra University. The researchers employed the descriptive approach using the survey method and designed a questionnaire to assess the challenges in planning and designing training programs, implementing training programs, and evaluating training programs. After verifying the validity and reliability of the questionnaire, it was administered to the entire study population, which consisted of 37 academic leaders. The number of respondents was 28 members, representing 78% of the study population. The study reached the following findings: The challenges faced by the Academic Training and Development Center in delivering training programs for academic leaders at Al-Mahra University, across the main fields of planning and designing training programs, implementing training programs, and evaluating training programs, were rated as significant. No statistically significant differences were found at a significance level of (0.05) between the mean scores of the study sample concerning the challenges of the Academic Training and Development Center in delivering training programs for academic leaders, attributed to the variables of college type (Humanities vs. Applied Sciences), academic rank (Professor, Associate Professor, Assistant Professor), and job position (Dean, Vice Dean, Head of Department). The study proposed several recommendations that could contribute to addressing the challenges of delivering training programs for academic leaders at Al-Mahra University.